Kegagalan Sosialisme Africa (African Socialism) Tanzania dan Pengaruhnya terhadap Eksploitasi Sumber Daya Alam Tambang oleh Inggris (2015-2020) - Galuh, Ni Made Kayika; Susanto, Siti Rokhmawati (Intermestic: Journal of International Studies, 2023)
ABSTRAK Tulisan ini berbicara mengenai kegagalan African Socialism Tanzania dalam menghindarkan negara dari eksploitasi sumber daya tambang oleh Inggris pada tahun 2015-2020. African Socialism adalah ideologi pembangunan Tanzania yang diimplementasikan dalam praktik politik dan ekonomi. Prinsip “sosialis” berarti kontrol pemerintah Tanzania terhadap ekonomi negara untuk menghindari “kapitalis” yaitu pihak yang mengakumulasi kapital di atas kepentingan masyarakat Tanzania. Tanzania mengedepankan kebijakan sosialisme-demokratis yang berfokus pada 1) absensi eksploitasi, 2) kontrol produksi oleh pemerintah dan para pekerja, serta 3) ditegakkannya demokrasi. Namun, pada era presiden John Magufuli, kasus-kasus eksploitasi tambang oleh perusahaan Inggris justru meningkat. Magufuli yang mengimplementasikan African Socialism melalui sistem ekonomi nasionalis gagal dalam mengeluarkan Tanzania dari kategori least developed country. African Socialism seharusnya menjadi ideologi pembangunan negara yang menonjolkan kemandirian dan asertivitas Tanzania dalam menghindari eksploitasi neokolonialisme. Anomali ini mengarahkan pada pertanyaan penelitian mengapa African Socialism gagal dalam menghindarkan sumber daya alam tambang Tanzania dari posisi tereksploitasi oleh Inggris pada tahun 2015-2020. Pertanyaan tersebut diteliti secara eksplanatif dengan kerangka state failure theory. Tulisan ini menemukan bahwa pemerintah Magufuli keliru dalam mengimplementasikan African Socialism pada aspek politik dan ekonomi yang merupakan bentuk kegagalan pembangunan negara. Kegagalan tersebut memudahkan konsesi pemerintah dan perusahaan Inggris terhadap sumber daya tambang Tanzania. Kata kunci: African Socialism, eksploitasi, Inggris,state failure, Tanzania. ABSTRACT This paper examines the failure of Tanzania’s African Socialism which leads the country entrapping into exploitation of mining resources by the British government in 2015-2020. African Socialism is Tanzanian development ideology that is adressed to conduct political and economic practices. “Socialist” principles refer to the ability of Tanzanian government in control of the domestic economy, and to avoid capitalist actors, namely those who accumulate capital above the interests of the Tanzanian people. Tanzania puts forward socialist-democratist policies focusing on 1) the absence of exploitation, 2) control of production by the government and workers, and 3) upholding democracy. However, during the era of President John Magufuli, cases of mining exploitation by the British companies have increased. Magufuli, who implemented African Socialism through a nationalist economic system failed to remove Tanzania from the category of least developed country. African Socialism should be the country’s development ideology that emphasizes Tanzania’s independence and assertiveness in avoiding the exploitation of neocolonialism. This anomaly directs to the research question on why African Socialism failed to prevent Tanzania’s natural mining resources from being exploited by the British in 2015-2020. The question is examined explanatively with the framework of state failure theory. This paper finds that the Magufuli government was intentiously incorrect in implementing African Socialism, partculary in the context of politics and economy, which exemplifies the form of state-building failure. The failure eased British government and corporate concessions to Tanzania’s mining resources. Keywords: African Socialism, exploitation, United Kingdom, state failure, Tanzania.